2008
DOI: 10.1145/1455248.1455249
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of combinatorial structure on congestion games

Abstract: We study the impact of combinatorial structure in congestion games on the complexity of computing pure Nash equilibria and the convergence time of best response sequences. In particular, we investigate which properties of the strategy spaces of individual players ensure a polynomial convergence time. We show that if the strategy space of each player consists of the bases of a matroid over the set of resources, then the lengths of all best response sequences are polynomially bounded in the number of players and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
250
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(251 citation statements)
references
References 13 publications
1
250
0
Order By: Relevance
“…On the other hand, Fabrikant et al [10] have studied the complexity of computing Nash equilibria in general congestion games proving that such a problem is PLS-complete. Ackermann et al [1] have shown that such result still holds if we restrict to unweighted congestion games with linear delay functions. From these results it follows that there exist linear congestion games with initial states such that any improvement sequence starting from these states needs an exponential number of steps to reach a Nash equilibrium.…”
Section: Related Workmentioning
confidence: 74%
See 3 more Smart Citations
“…On the other hand, Fabrikant et al [10] have studied the complexity of computing Nash equilibria in general congestion games proving that such a problem is PLS-complete. Ackermann et al [1] have shown that such result still holds if we restrict to unweighted congestion games with linear delay functions. From these results it follows that there exist linear congestion games with initial states such that any improvement sequence starting from these states needs an exponential number of steps to reach a Nash equilibrium.…”
Section: Related Workmentioning
confidence: 74%
“…Moreover from their completeness proof and from previous results about local search problems, it follows that there exist congestion games with initial states such that any improvement sequence starting from these states needs an exponential number of steps in order to reach a Nash equilibrium. More recently, Ackermann et al [1] show that the previous negative result holds even in the restricted case of linear unweighted congestion games. Furthermore, as already remarked, in the more general setting of weighted congestion games Nash equilibria may not exist.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In particular, the problem of computing a pure Nash equilibrium has been shown to be PLS-complete in congestion games by Fabrikant et al (2004) and in some of their special cases by Ackermann et al (2008), where congestion games, introduced by Rosenthal (1973), is a well-known and significative class of games represented in succinct form for which existence of pure Nash equilibria is always guaranteed. Moreover, the problem of computing a (mixed) Nash equilibrium has been shown to be PPAD-complete for any number of players (Chen et al 2009;Daskalakis et al 2009;Daskalakis and Papadimitriou 2005), even in games represented in standard normal form, i.e., by explicitly listing the utility of each player in any possible strategy profile.…”
Section: Introductionmentioning
confidence: 99%